Crafting a single cloth : an essay presented in partial fulfilment for the degree of Master of Design, Massey University, Wellington, New Zealand - Kim, Juran (Massey University, 2015)
Pattern-making and garment construction is often an over-looked practice within the fashion industry. This practice-led design project seeks to highlight the craft of pattern-cutting and how it can be used as an alternative method for clothing design. Through an iterative and 'risky' design method, one-piece pattern-construction is explored to create a new fashion aesthetic that was influenced by the cocoon. Experimentations with alternative uses of felt addressed some of the challenges faced when working with a single cloth. New processes were developed to create a more efficient, economical and holistic approach to garment design and construction. These investigations lead to the development of three evolving garments. Transitional aspects in each design encourage user engagement and introduce weavers to rethink their relationship with their clothing. These alternative methods clearly embedded in 'slow fashion' principles.
Keywords: Pattern design of clothing; Fashion design; Clothing and dress Pattern design